KERAGAAN KEDELAI (Glycine max (L) merril) GENERASI M1 VARIETAS ANJASMORO HASIL RADIASI SINAR GAMMA - ISNAINI ISNAINI; ASLIM RASYAD; DIRGA OKTA FIANDA (Jurnal Agroteknologi, 2020)
The purpose of this research was to find out the diversity of Anjasmoro variety soybean of M1 generation resulted from gamma-ray radiation on its various phenotype characters. A total of 300 seeds were radiated with Isotope and Radiation Technology Application from National Nuclear Power Agency at Pasar Jumat, South Jakarta, then planted in the experimental garden of Agriculture Faculty, Riau University. The dosage of irradiation used was 100 Gy, 150 Gy, 200 Gy, and 250 Gy also M0 as an ancestor. The quantitative and qualitative observation was made as such flowering age, harvest age, plant height, amount of seeds per plant, seeds weight per plant and growth type. The data were analyzed with variance analysis then continued with Duncan’s New Multiple Range Test on a 5% level. The diversity component was analyzed with homogeneity of variance according to the Levene test procedure. The result shows gamma-ray radiation is causing diversity on Anjasmoro variety on quantitative characters such as flowering age, harvest age and seed weight per plant. The vast diversity has happened on irradiation dosage of 200Gy.